A new species of Thismia (Thismiaceae) from Yunnan, China - Li, Hong-Qing; Bi, Yu-Ke (Phytotaxa, 2013)
Thismia Griffith (1844: 221) usually grows among leaf litter in shady wet forests and comprises 47 small mycoheterotrophic species (Chiang & Hsieh 2011, Mancinelli et al. 2012). Individual plants live underground through most of the year, only emerging briefly to flower and fruit after periods of heavy rain (Ho et al. 2009). Although several species have been described in temperate regions, Thismia occurs mainly in tropical portions of America and Asia.